Relationship between the Incidence of Angular Leaf Spot and Yield Losses of Red Kidney Bean in the Field - Parichut Junplang; Narong Singburaudom; Pairoj Jungbhanich; Surapon Oupadissakoon (Agriculture and Natural Resources, 1994)
The relationship between disease severity and yield lossses of 6 varieties of red kidney bean had been conducted both in rainny and dry season in the field. The results of statistical analysis revealed the existence of the negative correlation between disease severity and garonomic characters. It indicated that as the dissease severity 4 increased, height at maturity, day to maturity, number of pods per plant, number of diseasse-free pods per plant, number of seeds per pods of non infected and infected pods, 100 seeds weight and grain yield were decreased. The angular leaf spot disease reduced yield of red kidney beanin rainny season to 59.44, 88.84, 140.09 and 177.33 kg/rai and 44.56, 71.43, 84.87 and 100.13 kg/rai in dry season when the level of disease severity increased to 2, 3, 4 and 5 respectively. The results of this study suggested that the assessment of yield losses of red kidney bean due to angular leaf spot disease in rainny season can be estimated by linear regression Ŷ = 466.07 - 42.53 x and Ŷ = 375.59 - 24.02 x for dry season. (where Ŷ is estimated gain yield and is the observation of disease rating based on percent of infected leaf area.)